2017
DOI: 10.21608/puj.2017.4736
|View full text |Cite
|
Sign up to set email alerts
|

Curcuma longa extract nanoemulsion preparation and demonstration of its in vitro activity against Schistosoma mansoni cercariae, schistosomules and adult stages

Abstract: Background: Continuous attempts are being made to develop new and more effective drugs for treatment of schistosomiasis. Curcuma longa is a medicinal plant that contains yellow pigments known as curcuminoids (curcumin, bidesmetoxi-curcumin and monodesmetoxi-curcumin), with curcumin as the highest component. The main biological effect depends on curcumin content. Curcumin has low bioavailability and poor-water solubility. Preparation of C. longa (Cl) nanoemulsion was attempted to enhance solubility and bioavail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, curcumin has low bioavailability and poor water solubility. Thus, Aly et al [ 60 ] tried to increase its solubility and permeability through the cellular membrane by making a nanoemulsion of Curcuma longa extract (i.e., the curcumin plant source). The nanoemulsion showed an effect against adults of S. mansoni in vitro (especially males).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, curcumin has low bioavailability and poor water solubility. Thus, Aly et al [ 60 ] tried to increase its solubility and permeability through the cellular membrane by making a nanoemulsion of Curcuma longa extract (i.e., the curcumin plant source). The nanoemulsion showed an effect against adults of S. mansoni in vitro (especially males).…”
Section: Resultsmentioning
confidence: 99%
“…However, in this work, the death of females was only possible in a high concentration of the nanoformulation (100 µg/mL). Every dosage tested was also effective against young forms (esquistosomules) [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…They showed that this compound significantly reduced parasite load and inflammation in mice with no toxicity [ 58 ]. Investigation of the anthelmintic effects of CUR-NE on Schistosoma mansoni cercariae, schistosomules and adult stages, revealed optimal activity against the adult stage with decreased motor activity of the worms [ 59 ]. The protoscolicidal effects of curcumin and nanocurcumin have been shown in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is known that the use of Tween 80 (HLB = 15) is categorized as an O/W surfactant that has a higher solubility in the aqueous phase than in the organic phase (Sahlan et al 2018 ). It is recognized that Tween 80 contains a lipophilic polysorbate group facing the lipophilic core of the curcumin micelle and a hydrophilic polyoxyethylene group facing hydrophilic solvents (Aly et al 2017 ), making it suitable for use to encapsulate curcumin from Curcuma longa L. (CUR).…”
Section: Discussionmentioning
confidence: 99%
“…Turmeric has several active compounds, with an emphasis on curcuminoids, which include curcumin (77% of curcuminoids), demethoxycurcumin (18%), and bisdemethoxycurcumin (5%), among them, the most important is curcumin, which corresponds to about 3–4% of the plant (Aly et al 2017 ). This phytoconstituent has several therapeutic effects, such as, anti-inflammatory, antitumor, and antimicrobial action for several microorganisms, among them, gram-negative and gram-positive bacteria (Alves et al 2017 ; Karimi et al 2018 ; Reddy et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%